Effect of the Addition of Egg White and Maltodextrin on the Characteristics of Dayak Onion Powder (Eleutherine palmifolia) by Foam Mat Drying Method - Rosda, Sabila; Rosida, Rosida (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Dayak onion is a plant that has antioxidant content and chemical components that can be used as spices, flavor enhancers, fragrances, and food preservatives whose use is limited. Dayak onions that are easily damaged are processed into powder to make them more durable. The manufacture of powder products is carried out using the foam mat drying method with the addition of foaming agent, namely egg white, and foam stabilizer, namely maltodextrin. This study aims to determine the effect of the addition of egg whites and maltodextrin on the physicochemical and organoleptic characteristics of Dayak onion powder by the foam mat drying method. This study used a two-factor Complete Random Design (CRD) with three replicates. The observation data was processed using ANOVA at a confidence level of 5%, if there is a significant influence, a further DMRT test of 5% is carried out. The results showed that there was a significant interaction between the addition of egg white and maltodextrin in different moisture content, phenol content, and solubility. The best treatment was obtained with the addition of 8% egg white and 15% maltodextrin with 7.32% moisture content; 2.11% ash content; 51.08% antioxidant activity; 3.37 mg GAE/g phenol content; 46.65% solubility; 54.03 L; 21.00 a*; 11.43 b*; and color hedonic score 3.96 (quite red); aroma hedonic score 3.36 (slightly scented of Dayak onions); texture hedonic score 2.92 (slightly rough); 0.01% flavonoid content; and 9.35 ppm anthocyanin content.